Gay and Lesbian Health Agendas - Gomes, Romeu (2021)
The study aimed to validate the agendas claimed by representatives of homosexual groups aimed at providing comprehensive health care for gays and lesbians. For this, a matrix of health agendas was created, based on the consultation of a collection of another study, consisting of 25 narratives from representatives of 16 groups in ten Brazilian capitals. The agendas were considered validated from the average of scores equal to or greater than seven and standard deviation equal to or less than two. The validated agendas were related to the following themes: physical or psychological violence; attention to lesbians, related to uterine and breast cancers; mental health; training of health professionals; prevention and attention focused on AIDS; assisted reproduction for lesbians; attention to gays related to urological and proctological care; development of informational materials on general health and information and treatment of sexually transmitted infections. It is concluded that gay and lesbian movements can be important actors in the field of public health, not only indicating guidelines to be considered in policies and planning aimed at the health of their members but can also be mediators between health professionals and homosexuals who seek care from these professionals.